The impact of environmental management accounting on the decision making: A Case study for (RASCO) - ABDALMAJEED, Eltaib Elzarrouk (مجلة الدراسات الاقتصادية, 2021)
Abstract The concerns of human societies about the environment have increased nowadays due to technological development. The environment variations could influence human beings as well as their activities including the industrial development. This study, therefore conducted in order to explore the impact of environmental management accounting on the decision making in Ras Lanuf Oil and Gas Processing Company (RASCO) in Libya. To achieve the objectives of the study, a questionnaire has been developed to gather the data from respondents totaled (69) individuals employed at the (RASCO). The Statistical Package for Social Sciences (SPSS) program was used to analyze the data and test the hypothesis. Subsequently, a several results were reached including that the environmental management accounting significantly affects the decision making in (RASCO)